2016
DOI: 10.1021/acs.jced.6b00340
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Anionic Dyes from Aqueous Solutions by Cellulose-Based Adsorbents: Equilibrium, Kinetics, and Thermodynamics

Abstract: A novel cellulose (CE)-based adsorbent was synthesized by polyacrylamide grafted quaternized cellulose (PAM-g-QC) to remove anionic dyes. The elemental analysis results showed that there were abundant amino groups on adsorbents and scanning electron microscopy indicated the structure was porousproperties that were a benefit to increase the adsorption ability. The adsorption ability was specifically investigated in different temperatures. Adsorption isotherms including the Langmuir, Freundlich, and Temkin isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…CNF-GnP was able to adsorb both cationic MB and anionic CR and yielded higher uptake values compared to recent studies using cellulose, activated carbon, graphene, and CNT-based composites. Polyaniline@GO-multiwalled carbon nanotube nanocomposite 66.67 [44] Nickel nanoparticles/porous carbon-carbon nanotube hybrids 312 [50] Chitosan hydrogel beads impregnated with CNT 450.4 [51] 3D rGO/L-Cys hydrogel 660 [52] Functionalized multiwalled carbon nanotubes 148 [53] Graphene/cellulose nanofibers 227.27 [28] Polyacrylamide grafted quaternized cellulose 349.28 [54] GO/calcium alginate composites 181.81 [55] CaCO 3 −cellulose aerogel 75.81 [56]…”
Section: Effect Of Initial Dye Concentration and Adsorption Isothermmentioning
confidence: 99%
“…CNF-GnP was able to adsorb both cationic MB and anionic CR and yielded higher uptake values compared to recent studies using cellulose, activated carbon, graphene, and CNT-based composites. Polyaniline@GO-multiwalled carbon nanotube nanocomposite 66.67 [44] Nickel nanoparticles/porous carbon-carbon nanotube hybrids 312 [50] Chitosan hydrogel beads impregnated with CNT 450.4 [51] 3D rGO/L-Cys hydrogel 660 [52] Functionalized multiwalled carbon nanotubes 148 [53] Graphene/cellulose nanofibers 227.27 [28] Polyacrylamide grafted quaternized cellulose 349.28 [54] GO/calcium alginate composites 181.81 [55] CaCO 3 −cellulose aerogel 75.81 [56]…”
Section: Effect Of Initial Dye Concentration and Adsorption Isothermmentioning
confidence: 99%
“…The pseudo-first-order kinetic model (Eq. 2) (Wang et al 2016) and pseudo-second-order kinetic model (Eq. 3) (Wang et al 2016) were expressed in linear form as follows,…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Yu et al (2016) studied carboxylated cellulose nanocrystals for their use as cationic dye adsorbents. Wang et al (2016) synthesized polyacrylamide grafted quaternized cellulose by an inverse emulsion method, and the product was able to adsorb Eriochrome blue SE and Congo red dyes at the level of 349 mg·g -1 and 380 mg·g -1 , respectively. Moreover, surface quaternized cellulose nonfibrils exhibited good dye adsorption capacity and recyclability (Pei et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Salama et al presented carboxymethyl cellulose‐ g ‐poly(2‐(dimethylamino) ethyl methacrylate) hydrogel as an adsorbent for dye removal . Interesting recent studies about the use of cellulose‐based materials as adsorbents are reported by Wang et al Further, important highlights are described in literature about the use of peptide‐based hydrogels as adsorbents.…”
Section: Introductionmentioning
confidence: 99%